1966
DOI: 10.1139/e66-077
|View full text |Cite
|
Sign up to set email alerts
|

Rb/Sr AGE AND GEOLOGICAL SETTING OF THE HOLYROOD GRANITE, SOUTHEAST NEWFOUNDLAND

Abstract: The Precambrian Holyrood granite of southeastern Newfoundland is of particular geological interest, because of its tectonic position on the easternmost exposed flank of the Appalachian mobile belt. Although previously considered to have been emplaced during the Grenville orogeny, this granite yields a Rb/Sr isochron age of 574 ± 11 million years (m.y.). Tectonic and sedimentary events that followed the granite emplacement, and that preceded the deposition of nonconformably overlying fossiliferous Lower Cambria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…They suggested that the similarity of this date to that of the Swift Current Granite indicated a genetic link between them. They also pointed out that its similarity with the 590 f 11 Ma date for the Holyrood Granite (McCartney et al 1966) provides evidence for coeval plutonic and volcanic activity throughout the Avalon Terrane. We agree with this suggestion, although their data regress to 597: : : Ma and are not colinear, and caution is advised in using these dates.…”
Section: Previous Geochronological Studies Of the Newfoundlandmentioning
confidence: 92%
See 1 more Smart Citation
“…They suggested that the similarity of this date to that of the Swift Current Granite indicated a genetic link between them. They also pointed out that its similarity with the 590 f 11 Ma date for the Holyrood Granite (McCartney et al 1966) provides evidence for coeval plutonic and volcanic activity throughout the Avalon Terrane. We agree with this suggestion, although their data regress to 597: : : Ma and are not colinear, and caution is advised in using these dates.…”
Section: Previous Geochronological Studies Of the Newfoundlandmentioning
confidence: 92%
“…to 597 f 42 Ma (Fairbairn 1965in McCartney et al 1966, giving a recalculated age of 580 f 42 Ma. Stukas and Reynolds (1976), using 40Ar139Ar incremental heating, reported an age "in the vicinity of 800 Ma" for feldspars from a rhyolitic ash-flow tuff near the western flank of the Harbour Main Group.…”
Section: Previous Geochronological Studies Of the Newfoundlandmentioning
confidence: 99%
“…Newfoundland was considered to lack equivalents of the gneiss complexplatformal metasedimentary rock association, but had comparable molasse-type and CambrianOrdovician successions, and numerous volcanic and flyschoid sedimentary assemblages (e.g., Love Cove, Harbour Main, Connecting Point, and Conception groups) that considered correlative with the Coldbrook Group. But in Newfoundland, the volcanic assemblages were, in addition, locally intruded by the Holyrood granite of known Precambrian age (574AE11 Ma, Rb/Sr, McCartney et al, 1966;609AE11 Ma, Rb/Sr, Frith and Poole, 1972), and the molasse-type facies were known to be associated with younger, more alkaline volcanic rocks (Bull Arm Formation; e.g., Hughes and Bru¨ckner, 1971). …”
Section: Recognition Of the Avalonian Arcmentioning
confidence: 99%